“In The Light Of”: A Corpus-Based Analysis of Lexical Bundles in Two EU-Related Registers - Jablonkai, Réka (Working Papers in Language Pedagogy, 2009)
This paper is a report on a corpus-based analysis of two EU-related registers. The study aims to explore the discourse of official EU texts and online EU news applying a frequency-based approach suggested by Biber and Conrad (1999). The concept developed and applied for this approach is the lexical bundle which has been found characteristic for specific registers. Based on the investigation of the most frequent 50 single-word items and the structural and functional analysis of the identified lexical bundles in official EU texts and online EU news texts, the discourse of the two EU-related registers are found to differ considerably. Discourse in official EU texts can be characterised in contrast to online EU news texts by a higher proportion of content words in the top 50 single-word lexical items, more frequent use of lexical bundles in general, very few identical lexical bundles and by a significantly different distribution of lexical bundles across structural types and functional categories. Besides the description of the two EU-related registers, pedagogical implications are also discussed.